CHANGES IN PLASMA LIPID COMPOSITION IN PATIENTS WITH ESSENTIAL HYPERTENSION - A. V. Govorin; N. V. Lareva; B. S. Hyshiktuyev; A. P. Filev (Российский кардиологический журнал, 2003)
To examine the relation between serum fatty acids, blood pressure and heart failure in hypertensive patients we conducted a study of 58 patients with essential hypertension (mean age 45,1 ± 9,4 years) and 22 healthy subjects. It was established, that in essential hypertension the levels of saturated and monounsaturated fatty acids increased and the amount of polyunsaturated fatty acids decreased. Aforesaid changes were different within some classes of fatty acids: among saturated acids the levels of myristic and palmitic acids increased and the concentration of stearic acid decreased. Among polyunsaturated acids the amount oflinolenic and a-linolenic acids decreased and the level of arachidonic acid increased. Aforesaid changes correlated with main parameters of ambulatory blood pressure monitoring and structural and functional state of left ventricle.